DEVELOPMENT OF ECOTOURISM IN THE REGION OF GJIROKASTRA, ONE MORE OPPORTUNITY FOR SUSTAINABLE DEVELOPMENT - Armand HYSI; Lorenc Kociu; Romeo MANO (European Scientific Journal, ESJ, 2015)
Ecotourism is considered as one of the forms of tourism, which provides a sustainable development in long-term periods. To be successful, ecotourism should promote sustainable development by means of the support of activities that create the possibility for the local residents and tour operators to increase their incomes and improve living standards. Ecotourism must do more than simply creating a number of activities just to attract the tourists, offering to the tourists a chance to interact with nature in such a way as to protect flora and fauna parts, allowing future generations enjoy these natural resources. Through this work will be given reasons that support the development of ecotourism in the region of Gjirokastra, and combined with cultural tourism will bring a greater economic, environmental and social impact. To successfully realize this work are used statistics from different institutions, interviews with entrepreneurs in the tourism sector in the region of Gjirokastra in order to identify the problems and opportunities in this region, also are used published materials related to ecotourism and its development in different regions.